Síntesis asistida por ultrasonido de Pirazolo[3,4-b]Piridinas policíclicas fusionadas - Trilleras, Jorge; Ríos-De-La-Rotta, Freddy; Pedroza-García, Luis-Felipe (Revista Científica, 2023)
This work describes a synthetic methodology developed to obtain fused polycyclic pyrazolo[3,4-b]pyridines. The synthesis was carried out in two stages, starting with the preparation of α,β-unsaturated naphthones and their subsequent cyclocondensation with 5-amino-1-phenyl-3-methyl-1H-pyrazole. The advantages of this approach include simplicity, atomic efficiency, selectivity, and good yields with minimal environmental impact. The synthetic route is aimed at obtaining N-heterocycles with specific points of structural diversification that are of interest for later exploration of their biological properties.